Untangling the connection between endocrine disrupting compounds, river pollution classes, and socioeconomic factors - Sze Yee, Wee; Didi Erwandi Mohamad, Haron; Muhammad Raznisyafiq, Razak; Norbaya, Hashim; Nasehir Khan E.M., Yahaya; Nirmala Devi Kerisnan, Kerishnan; Raja Baharudin Raja, Mamat; Ahmad Zaharin, Aris (Springer Nature, 2025)
The contamination of endocrine disrupting compounds (EDCs) stands as an emerging environmental concern, leading to subsequent environmental and human exposure. A comprehensive analysis identified a total of 18 EDCs, including pharmaceuticals, hormones, and plasticizers, in Malaysian rivers classified into distinct pollution classes: “Clean”, “Moderately Polluted”, and “Polluted”. The highest concentration of EDCs was observed in the “Moderately Polluted” Kim Kim River, notably containing 16.25 µg/L of caffeine. Caffeine exhibited ubiquitous presence across all pollution classes, with the Klang River (“Polluted”) showing the peak concentration at 13.62 µg/L. In contrast, the “Clean” Kuantan River displayed the highest EDC concentration at 1.28 µg/L of bisphenol A. All individual EDCs posed negligible ecological risks, with RQ values below 0.01 (RQm < 8.70 × 10⁻3). Similarly, negligible risks were observed for most EDCs under the worst-case scenario (RQex < 2.36 × 10⁻3). Noteworthy findings included the detection of previously undetected pharmaceuticals such as diphenhydramine on a global scale. Variability in the distribution of EDCs among river pollution classes exhibited statistically significant differences in their concentrations. The socioeconomic impact was evident, with gross domestic product (GDP) and population size positively influencing EDC concentrations, emphasizing the interconnected dynamics of urbanization, healthcare development, and pharmaceutical consumption. Additionally, the study identified negligible to low ecological risks associated with both individual and combined exposures to EDCs under general and worst-case scenarios. However, higher EDC risks were observed even in rivers classified as “Clean” or “Moderately Polluted”, highlighting the need for more comprehensive monitoring strategies that account for emerging contaminants.